Effect of liquidity risk on the profitability of Islamic banks listed in Dhaka Stock Exchange: a comparative study between Shahjalal Islami Bank Limited and other listed banks - Rashid, Bushra Binte (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.